2018
DOI: 10.1002/agr.21574
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brand equity on the financial performance of marketing cooperatives

Abstract: Because of inherent constraints, few farmer cooperatives use branding to pursue differentiation and competitiveness in the agri-food industry. Considering the complete lack of applied research on the brand-performance relationship for farmer cooperatives, it is unknown if branding is even profitable. This paper addresses the gap in our understanding with a novel panel study of 707 US marketing cooperatives for the 2005-2011 period. Informed by lagged observations of trademark and service mark data, the empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
0
29
0
2
Order By: Relevance
“…In contrast to the investor-owned firm (IOF), which strives to maximize return on investment for its shareholders, a cooperative is a user-owned, user-controlled business from which benefits are derived and distributed equally based on use. Existing research evaluates cooperative financial performance as one would profit-maximizing IOFs and fails to account for empirical complications due to endogeneity of governance and performance [4][5][6][7][8][9]. Moreover, as the (dual) function of cooperatives (i.e., profitability and member benefits) is distinct from that of IOFs [10][11][12][13], the same governance recommendations may not apply and alternative performance measures may be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the investor-owned firm (IOF), which strives to maximize return on investment for its shareholders, a cooperative is a user-owned, user-controlled business from which benefits are derived and distributed equally based on use. Existing research evaluates cooperative financial performance as one would profit-maximizing IOFs and fails to account for empirical complications due to endogeneity of governance and performance [4][5][6][7][8][9]. Moreover, as the (dual) function of cooperatives (i.e., profitability and member benefits) is distinct from that of IOFs [10][11][12][13], the same governance recommendations may not apply and alternative performance measures may be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Hanf and Schweickert [7] showed that member heterogeneity increases all challenges which were mentioned above. [35] The business principles of (wine) cooperatives as well as the internal structure and consequent problems often lead to a strong member orientation [14]. Furthermore, cooperative members are of different size and some are full-time grape producers whereas others are only active part time in viticulture.…”
Section: Wine Cooperatives In Germanymentioning
confidence: 99%
“…Cooperatives which follow the approach of sustainable production should use this as an outstanding feature in communication with customers. Furthermore, the usage of the "farmer-owned" attribute can provide a marketing advantage over non-cooperatives [14]. Consumers might associate the cooperative with certain social values such as democracy, equality, or solidarity, which can also provide a marketing advantage [14,66].…”
Section: Differentiation and Differentiation Focus Strategymentioning
confidence: 99%
See 2 more Smart Citations